Emergency air evacuation of patients with acute respiratory failure due to SARS-CoV-2 from Mayotte to Reunion Island. Issue 48 (3rd December 2021) - Berguigua, Hamza; Iche, Ludovic; Roche, Philippe; Aubert, Cyril; Blondé, Renaud; Legrand, Antoine; Puech, Bérénice; Combe, Chloé; Vidal, Charles; Caron, Margot; Jaffar-Bandjee, Marie-Christine; Caralp, Christophe; et al.
Abstract : Abstract: In February 2021, an explosion of cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia overwhelmed the only hospital in Mayotte. To report a case series of patients with acute respiratory failure (ARF) due to SARS-CoV-2 who were evacuated by air from Mayotte to Reunion Island. This retrospective observational study evaluated all consecutive patients with ARF due to SARS-CoV-2 who were evacuated by air from Mayotte Hospital to the intensive care unit (ICU) of Félix Guyon University Hospital in Reunion Island between February 2, and March 5, 2021. A total of 43 patients with SARS-CoV-2 pneumonia were evacuated by air, for a total flight time of 2 hours and a total travel time of 6 hours. Of these, 38 patients (88.4%) with a median age of 55 (46–65) years presented with ARF and were hospitalized in our ICU. Fifteen patients were screened for the SARS-CoV-2 501Y.V2 variant, all of whom tested positive. Thirteen patients (34.2%) developed an episode of severe hypoxemia during air transport, and the median paO2 /FiO2 ratio was lower on ICU admission (140 [102–192] mmHg) than on departure (165 [150–200], P  = .022). Factors associated with severe hypoxemia during air transport was lack of treatment with curare ( P  = .012) and lack of invasive mechanical ventilation ( P  = .003). Nine patients (23.7%) received veno-venous extracorporeal membrane oxygenation support in our ICU. Seven deaths (18.4%) occurred in hospital. Emergency air evacuation of patients with ARF due to SARS-CoV-2 was associated with severe hypoxemia but remained feasible. In cases of ARF due to SARS-CoV-2 requiring emergency air evacuation, sedated patients receiving invasive mechanical ventilation and curare should be prioritized over nonintubated patients. It is noteworthy that patients with SARS-CoV-2 pneumonia related to the 501Y.V2 variant were very severe despite their young age.